2018
DOI: 10.3324/haematol.2018.191213
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of the miR-17-92 cluster is involved in the growth-promoting effects of MYB in human Ph-positive leukemia cells

Abstract: MicroRNAs, non-coding regulators of gene expression, are likely to function as important downstream effectors of many transcription factors including MYB. Optimal levels of MYB are required for transformation/maintenance of BCR-ABL1-expressing cells. We investigated whether MYB silencing modulates microRNAs expression in Philadelphia-positive leukemia cells and if MYB-regulated microRNAs are important for the MYB addiction of these cells. 35 microRNAs were modulated by MYB silencing in chronic lymphoid and ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The canonical Wnt/β-catenin pathway is activated when the Wnt ligand binds to the Frizzled (FZD) receptor and its co-receptor from the low-density lipoprotein receptor-related protein 5/6 class (LRP5/6) (MacDonald et al, 2009). Previous studies have demonstrated that the miR-17-92 cluster could regulate Wnt signaling via directly targeting Wnt pathway components, such as FZD4 and LRP6 (Landskroner-Eiger et al, 2015) or the Wnt signaling inhibitors FRZB and HIPK1 (Wu et al, 2013; Spagnuolo et al, 2019). In addition, the miR-17-92 cluster could inhibit Wnt signaling via targeting E2F1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The canonical Wnt/β-catenin pathway is activated when the Wnt ligand binds to the Frizzled (FZD) receptor and its co-receptor from the low-density lipoprotein receptor-related protein 5/6 class (LRP5/6) (MacDonald et al, 2009). Previous studies have demonstrated that the miR-17-92 cluster could regulate Wnt signaling via directly targeting Wnt pathway components, such as FZD4 and LRP6 (Landskroner-Eiger et al, 2015) or the Wnt signaling inhibitors FRZB and HIPK1 (Wu et al, 2013; Spagnuolo et al, 2019). In addition, the miR-17-92 cluster could inhibit Wnt signaling via targeting E2F1.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of other transcription factors have been identified as direct regulators of MIR17HG transcription. Among the identified regulators, c-Myc, N-Myc, STAT3, STAT5, MYCN, MYB, Spi-1, Fli-1, Pim-1, cyclin D1, AML1, ETS1, ETS2, NKX3.1, and E2F family members activate (Fontana et al, 2007; Sylvestre et al, 2007; Yu et al, 2008; De Brouwer et al, 2012; Feuermann et al, 2012; Kayali et al, 2012; Thomas et al, 2013; Kabbout et al, 2014; Yang et al, 2015; Spagnuolo et al, 2019), whereas p53 and C/EBPβ suppress the transcription of MIR17HG (Yan et al, 2009; Yan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several transcription factors with a role in differentiation and proliferation control, have been found to transcriptionally activate miR-17-92, such as RUNX1, EGR2, p53, FLI1 and MYC 47,[63][64][65] (also see 66 ). Transcriptional activation of the miR-17-92 cluster by the transcription factor MYB is implicated in the growth-promoting effects of MYB in Ph-positive leukemia cells 67 . This direct activation of miR-17-92 by MYB was also observed in K562 cells.…”
Section: Tal1 and Mir-17-92 In Differentiationmentioning
confidence: 99%
“…Previous studies indicated that MYB transcription is mainly regulated through a transcriptional attenuation site within the first intron 14 , 15 . miRNAs including miR-150 and miR-17-92 can target MYB mRNA in a stage-specific manner 16 , 17 . PU.1 negatively regulates the c-myb promoter during granulocytic differentiation 18 .…”
Section: Introductionmentioning
confidence: 99%